Potret Perbankan Syariah Indonesia: Telaah Sejarah, Regulasi, Produk, dan Pengawasan - Febriyani Febriyani; Husna Karimah; Annisa Taqiyya Nurhaqiqiy; Mutammimah Mutammimah; Zainab Al-Kubra (Ikatan Da'i Indonesia, 2026)
Islamic banking is a financial system founded on Islamic legal principles that prohibits riba (usury), gharar (uncertainty), and maysir (gambling), while promoting justice and public welfare (maslahah). This study aims to analyze the development of Islamic banking in Indonesia from historical, legal, regulatory, product, and supervisory perspectives. The research employs a qualitative descriptive approach using the library research method. The data were collected from the Qur'an, Hadith, fatwas issued by the National Sharia Council of the Indonesian Council of Ulama (DSN-MUI), Law Number 21 of 2008 concerning Islamic Banking, the Compilation of Sharia Economic Law (KHES), as well as books, scholarly journals, and official publications of the Financial Services Authority (OJK) and Bank Indonesia. The findings indicate that Islamic banking originated from muamalah practices during the time of Prophet Muhammad ﷺ and has evolved into a modern financial system supported by a comprehensive national regulatory framework. Its operations are based on Sharia contracts and supervised by the DSN-MUI and the Sharia Supervisory Board (DPS) to ensure Sharia compliance. The study concludes that strengthening corporate governance, promoting product innovation, improving Islamic financial literacy, and enhancing human resource quality are essential factors for the sustainable development of Islamic banking in Indonesia.